Rapid Library Synthesis of Amphiphiles Based On a Dioxinone Scaffold and Identification of Nonlamellar Liquid Crystals - Fuse, Shinichiro; Nakamura, Kentarou; Mifune, Yuto; Marubayashi, Hironori; Hijikuro, Ichiro; Nojima, Shuichi; Tanaka, Hiroshi; Takahashi, Takashi (Synlett, 2014)
Linear and branched amphiphiles with different lengths of lipids and different numbers of hydroxyl groups were rapidly synthesized based on a dioxinone scaffold. The liquid crystalline (LC) properties of the synthesized amphiphiles in excess water were investigated by polarizing optical microscopy and small-angle X-ray scattering (SAXS) analysis. Novel β-keto ester based amphiphiles that formed non-lamellar, inverted LC phases were identified.
Keywords: multicomponent reaction; combinatorial chemistry; alkylation; nucleophilic addition; palladium